GIFs that glitch: eyeball aesthetics for the attention economy. Issue 1 (2nd July 2016) - Kane, Carolyn L.
Abstract: The most valuable gift you can give someone is attention. But does this same rule apply to the nonstop demand for attention marshalled through Internet technologies? Driven by an insatiable appetite for profit, scientific research in compression techniques are used to reduce data and economize signals to questionable extremes. Given this awareness, does one comply, paying attention to the point of exhaustion, offering endless hours of eyeball attention re-tweeting, re-blogging, and 'liking' so someone else may reap profit, or does one tweak the circuit and rewire the rules of the game? A number of contemporary artists have gravitated to the latter, reconfiguring otherwise functional Internet tools and interfaces into error-laden 'glitch art' and animated Graphic Interchange Format (GIFs). While these new glitch genres appear to offer nothing but meaningless fragments of polychromatic noise, they do in fact raise valuable questions regarding the material and economic logic of the Internet, normatively concealed from end users. I argue that certain uses of animated GIFs and glitch art offer an emergent visual rhetoric of anti-communication that marks, echoes, and offsets the progressive rationalization of aesthetics in modern culture and media.